A revision of the spirit loaches, genus Lepidocephalus (Cypriniformes, Cobitidae) - Deein G. (Magnolia Press, 2014)
Lepidocephalus has been assumed to include only two species and confined to peninsular Malaysia and Indonesia. How-ever, based on records and collections reported herein, the genus contains five species and is most common in the Chao Phraya basin of Thailand. Large rivers seem to be the preferred habitat, and difficulty in collecting these rivers may ac-count for the paucity of specimens in collections. The known range of these five species includes western and southern Borneo, Java, Sumatra, peninsular Malaysia, and central Thailand Copyright © 2014 Magnolia Press.